Pedagogy of the oppressed - Freire, Paulo, 1921-1997; Ramos, Myra Bergman; Macedo, Donaldo P. (Donaldo Pereira), 1950-; Shor, Ira, 1945- (New York : Bloomsbury Academic, 2018)
"First published in Portuguese in 1968, [this book] was translated and published in English in 1970. Paulo Freire's work has helped to empower countless people throughout the world and continues to possess a special urgency as the creation of a permanent underclass among the underprivileged and minorities in urban centers around the world continues. The 50th anniversary edition includes a new introduction by Donaldo Macedo, an afterword by Ira Shor, and interviews with Marina Aparicio Barberán, Noam Chomsky, Gustavo E. Fischman, Ramón Flecha, Ronald David Glass, Valerie Kinloch, peter Mayo, Peter McLaren, and Margo Okazawa-Rey to inspire a new generation of educators, students, and general readers for years to come."--Page [4] of cover.
Includes bibliographical references.
LTIC
Hye Trade International
In English, translated from the Portuguese.
Keywords: Education -- Philosophy; Popular education -- Philosophy; Critical pedagogy